Pursuing green growth in Asia and the Pacific - Chung, Rae Kwon; Quah, Euston; Gale Group; Ministerial Conference on Environment and Development in Asia and the Pacific (2005 Seoul, Republic of Korea). (Singapore Cengage Learning Asia, 2010)
Aims to develop the new paradigm for environmentally sustainable economic growth or 'green growth' in Asia and the Pacific. Discusses the present status of environmental sustainability, especially the issue of eco-efficiency of consumption and production patterns.
pt. 1. State of environmental sustainability in Asia and the Pacific -- pt. 2. Challenging issues of environmental sustainability in Asia and the Pacific -- pt. 3. New paradigm for green growth in Asia and the Pacific.
"The Fifth Ministerial Conference on Environment and Sustainable Development (MCED) in Asia and the Pacific was held on 24-29 March 2005 in Seoul, South Korea, with a theme of 'Achieving Environmentally Substainable Economic Growth'. In conjunction with the MCED, the Eminent Environmental Economists Symposium (EEES) on Green Growth in Asia and the Pacific was held, featuring a number of eminent environmental economists ... Another related conference was held on 8-9 November 2005 in Seoul, with the theme 'Achieving Environmentally Substainable Economic Growth : Eco-efficiency through Green Tax and Budget Reform'. This book comprises selected papers that were presented in both conferences."--Pref.
Electronic reproduction.
Keywords: Sustainable development -- Asia -- Congresses; Sustainable development -- Pacific Area -- Congresses; Environmental policy -- Asia -- Congresses; Environmental policy -- Pacific Area -- Congresses; Environmental protection -- Asia -- Congresses; Environmental protection -- Pacific Area -- Congresses; Economic development -- Environmental aspects -- Asia -- Congresses; Economic development -- Environmental aspects -- Pacific Area -- Congresses; Electronic books